Evaluation of Different Thermoanalytical Methods for the Analysis of the Stability of Naproxen-Loaded Amorphous Solid Dispersions - Edina Szabó; Anna Haraszti; Petra Záhonyi; Dániel Vadas; István Csontos; Zsombor Kristóf Nagy; Guy Van den Mooter; György Marosi (MDPI AG, 2022)
The aim of this research was to investigate three thermoanalytical techniques from the glass transition temperature (Tg) determination point of view. In addition, the examination of the correlation between the measured Tg values and the stability of the amorphous solid dispersions (ASDs) was also an important part of the work. The results showed that a similar tendency of the Tg can be observed in the case of the applied methods. However, Tg values measured by thermally stimulated depolarization currents showed higher deviation from the theoretical calculations than the values measured by modulated differential scanning calorimetry, referring better to the drug-polymer interactions. Indeed, the investigations after the stress stability tests revealed that micro-thermal analysis can indicate the most sensitive changes in the Tg values, better indicating the instability of the samples. In addition to confirming that the active pharmaceutical ingredient content is a crucial factor in the stability of ASDs containing naproxen and poly(vinylpyrrolidone-co-vinyl acetate), it is worthwhile applying orthogonal techniques to better understand the behavior of ASDs. The development of stable ASDs can be facilitated via mapping the molecular mobilities with suitable thermoanalytical methods.